PROTOTIPE TABUNG SEMPROT PUPUK CAIR BERBASIS WAHANA QUADCOPTER BAGI LAHAN TANAMAN PADI - Son Ali Akbar; Anton Yudhana (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2016)
Rice crop fertilization activities generally rely on based traditional of spray equipment. Their methods have used the influence of the traditional farmer on impact rice production. However, the problem facing paddies can touch by the farmer. In this research is providing the latest solutions with the application of modern vehicle technology UAV aircraft based on multirotor type (i.e., quadcopter). By quadcopter, brings appliance contains liquid fertilizer one compost can be spread through the air. The system of mutually connected between spray tube device and vehicle of quadcopter can be controlled the autonomous operate from a home based. The quadcopter can be brought liquid fertilizer to 1000 ml with two sprayers. Also, the research is a comparison of time and become discharge liquid fertilizer of the effectiveness this work on paddies farming.